Digital science magazine based on contextual learning on the polluted river topic - Saptiyah Saptiyah; Lukman Nulhakim; Dwi Indah Suryani (Department of Mathematics and Science Education, Faculty of Teacher Training and Education, University of Mataram. Jurnal Pijar MIPA colaborates with Perkumpulan Pendidik IPA Indonesia Wilayah Nusa Tenggara Barat, 2023)
This research is driven by the need for more utilization of opportunities for technological advances in the field of education, one of which is the creativity of educators in creating and using a learning media, resulting in less efficient learning implementation. digital science magazine (DSM) can be an alternative to interesting learning media that utilizes technology well. This study aims to determine DSM's validity and student attractiveness based on contextual learning on the theme of my polluted river. The method applied is Research and Development along with the ADDIE model (Analysis, Design, Development, Implement, and Evaluate). Material experts, media experts, and expert practitioners completed the validation assessment. At the same time, the assessment of attractiveness was carried out by students using student response questionnaires. Overall from the experts, the developed DSM obtained a validity level of 88.4% which is categorized as very valid. Based on the research, DSM, based on contextual learning developed, has a good level of validity and attractiveness so that it can be used in learning at school or independently at home by junior high school students.